2021
DOI: 10.1177/10556656211025406
|View full text |Cite
|
Sign up to set email alerts
|

Nasalance Scores for Normal Speakers of American English Obtained by the Nasometer II Using the MacKay-Kummer SNAP-R Test

Abstract: Objective: To establish nasalance score norms for adolescent and young adult native speakers of American English and also determine age-group and gender differences using the Simplified Nasometric Assessment Procedures (SNAP) Test-R and Nasometer II. Design: Prospective study using a randomly selected sample of participants. Setting: Greater Cincinnati area and Miami University of Ohio. Participants: Participants had a history of normal speech and language development and no history of speech therapy. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This is encouraging, as past study indicates that there may be more variation in ratings of male speech, 58 and the Nasometer has been shown to detect higher nasalance in females on /i/ vowelspresumably due to sex-related differences in velopharyngeal structures. 35 The lack of sex related differences may reflect the fact that this study population was largely pre-pubertal. As such, it is likely that the impact of the thickening of the velum, and lengthening of the levator veli palatini observed during puberty in males, 87 was minimal in the current study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is encouraging, as past study indicates that there may be more variation in ratings of male speech, 58 and the Nasometer has been shown to detect higher nasalance in females on /i/ vowelspresumably due to sex-related differences in velopharyngeal structures. 35 The lack of sex related differences may reflect the fact that this study population was largely pre-pubertal. As such, it is likely that the impact of the thickening of the velum, and lengthening of the levator veli palatini observed during puberty in males, 87 was minimal in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Sex and age were accounted for in the model because these factors can impact nasometry outcomes. 35 Fixed factors included in the model included stimulus type (bilabial, alveolar, velar, sibilant, Zoo passage), auditory-perceptual ratings (balanced resonance, mild, moderate, severe, profoundly hypernasal), sex (male, female), and cleft related diagnosis (Veau I, II, II, IV, submucous), and all interactions. Patient age was included as a covariate.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Woo and colleagues have shown, differences in measurement equipment can cause discrepancies of up to several percent, despite the same language tests being used [11]. This suggests that measurement standards should be checked and adjusted whenever there are significant changes in recording methods [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a slight increase in nasalance values of children with increased age (Ünal-Logacev et al, 2020;Alfwaress, 2022). Others have found no effect of age on nasalance (Bettens et al, 2017).…”
Section: Effect Of Age On Nasalancementioning
confidence: 99%